Land comprehensive carrying capacity and spatio-temporal analysis of the guangdong-Hong Kong-Macau Greater Bay Area - Wu, Zhanglan; Su, Yantao; Xiong, Mingliang (Frontiers in Environmental Science, 2022)
The Guangdong-Hong Kong-Macao Greater Bay Area (GBA) is one of the fastest growing and most dynamic regions in China. Changes in land comprehensive carrying capacity (LCCC) is of vital significance. In China, various studies have assessed LCCC, however, they majorly focused on single cities, with less studies focusing on urban agglomeration, particularly GBA. Based on social, economic, resource and technology aspects, we established an index system for evaluating LCCC by the entropy method. It analyses temporal and spatial evolution characteristics of LCCC from 11 cities in the GBA of China, 2009-2018. There are many social, economic, resource and technology differences among the 4 subsystems. We established that technology is the prominent factor in LCCC. With regards to LCCC, these cities have their respective strengths and weaknesses. On a temporal basis, there were rising trends in LCCC curves, with different degrees of the 11 cities. Spatially, LCCC is relatively high in central cities and it exhibits a declining pattern of the carrying capacity from the city center outwards. Therefore, regional collaborative efforts are vital for increasing LCCC.